ANÁLISE DOS PARÂMETROS DE CORPOS HÍDRICOS EM DIFERENTES PONTOS SITUADOS NO PARQUE DA LAGOA COMPRIDA EM AQUIDAUANA/MS - CANAVARROS, Caroline Duarte; POMPEU, Patrícia Vieira; IBANEZ, Fernando Martins; CORREA, Jonas de Souza (ANAIS DO ENIC, 2023)
-